Epidemiological Status and Pathogenetic Features of Renal Complications Associated with Post-Covid Syndrome - Khaytboyev Jurabek Azatboyevich; Rakhmanova Sanobar Sobirovna (Scientific Trends, 2024)
The aim of the study is to evaluate the condition and risk of renal complications associated with flat-sided syndrome within the framework of a review of existing scientific data. Materials and methods. The literature search carried out in the Internet resources: Cochrane databases Library, PubMed.gov, Elsevier.com, and Google Scholar. Analysis of the obtained data focused on the works published between 2020 and 2023. Results. After manuscript revision procedures, 20 scientific works selected that most fully reflect epidemiological status and pathogenetic features of renal complications associated with post-COVID syndrome. Conclusion. Post-COVID syndrome has a direct and indirect effect on renal function, leading to the development of acute and chronic renal complications. An important role in pathogenesis of these complications played by factors such as inflammatory response, endothelial dysfunction, hypoxia and hypercoagulation, including those characteristics of COVID-19.
Keywords: Post-covid syndrome; renal complications; epidemiology; COVID-19.